2009
DOI: 10.1016/j.electacta.2008.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Highly dispersed platinum nanoparticles on carbon nanocoils and their electrocatalytic performance for fuel cell reactions

Abstract: Highly graphitic carbon nanocoils (GCNC) were synthesized through the catalytic graphitization of carbon microspheres obtained by the hydrothermal carbonization of different saccharides (sucrose, glucose and starch) and were used as a support for Pt nanoparticles. The Pt nanoparticles were deposited by means of a polymer mediatedpolyol method. The Pt catalysts were characterized both physically (XRD, TEM, HRTEM and XPS) and electrochemically (electrooxidation of methanol in an acid medium). The electrocatalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…but rather still relate to the oxidation of the methanol molecules in the electrolyte [65][66][67]. In addition, Yajima et al [68,69] have studied the electro-oxidation of methanol on the Pt by virtue of in situ ATR-FTIR spectroscopy, and have found that the adsorbed CO, which is dehydrogenated species from methanol, is oxidized at the potential more positive than 0.6 V (RHE).…”
Section: Resultsmentioning
confidence: 97%
“…but rather still relate to the oxidation of the methanol molecules in the electrolyte [65][66][67]. In addition, Yajima et al [68,69] have studied the electro-oxidation of methanol on the Pt by virtue of in situ ATR-FTIR spectroscopy, and have found that the adsorbed CO, which is dehydrogenated species from methanol, is oxidized at the potential more positive than 0.6 V (RHE).…”
Section: Resultsmentioning
confidence: 97%
“…Regeneration experiments techniques, the carbonaceous materials obtained from the HTC process at lower temperature possessed numerous oxygen-containing groups on their surfaces and hence could have remarkable feature to be used as adsorbents for water purification [18,21]. Based on that, we chosen the chitosan as potential precursors within this process creatively instead of saccharides such as glucose, sucrose, starch and cellulose reported in many studies [22][23][24] due to an abundant amino functional groups in its structure. A new kind of attapulgite clay@ carbonized chitosan (ATP@CCS) nanocomposite adsorbent was prepared via the one-step HTC synthesis route at a mild temperature (180 • C), in which ATP plays the role as a template (low-cost and rich in nature) and the carbonization and functionalization will occur through the dehydration of the chitosan, leading to the formation of highly amino-functionalized carbonaceous shell coating the ATP.…”
mentioning
confidence: 98%
“…Način aktiviranja i vrsta prekursora direktno utiču na strukturu dobijenog aktivnog uglja, na poroznost i tip funkcionalnih grupa na površini [10]. Mnogi istraživači su bili usmereni kako na izmene, kao i na karakterizaciju površinskih funkcionalnih grupa ugljenikovih materijala u cilju poboljšanja ili poboljšanja njihovih primena [11][12][13] Specifična površina, pore, struktura i površina hemijskih funkcionalnih grupa poroznog ugljenika određuju primenu [14][15][16][17]. Porozni ugljenik sa svojim velikim adsorpcionim sposobnostima i visokom poroznošću su u širokoj upotrebi u raznim oblastima, kao što su nosači katalizatora, elektrodni materijal za baterije, industrijsko prečišćavanje, dobijanje nanokompozita itd.…”
Section: Uvodunclassified